Proton-coupled electron transfer reactivities of electronically divergent heme superoxide intermediates: a kinetic, thermodynamic, and theoretical study. Issue 25 (4th June 2021) - Mondal, Pritam; Ishigami, Izumi; Gérard, Emilie F.; Lim, Chaeeun; Yeh, Syun-Ru; de Visser, Sam P.; Wijeratne, Gayan B.
Abstract : Electronic characteristics of heme significantly influence the feasibility of hydrogen atom abstraction by synthetic heme superoxide moieties, shedding new light on analogous scenarios implicated in both biological and alternate energy applications. Abstract : Heme superoxides are one of the most versatile metallo-intermediates in biology, and they mediate a vast variety of oxidation and oxygenation reactions involving O2(g) . Overall proton-coupled electron transfer (PCET) processes they facilitate may proceed via several different mechanistic pathways, attributes of which are not yet fully understood. Herein we present a detailed investigation into concerted PCET events of a series of geometrically similar, but electronically disparate synthetic heme superoxide mimics, where unprecedented, PCET feasibility-determining electronic effects of the heme center have been identified. These electronic factors firmly modulate both thermodynamic and kinetic parameters that are central to PCET, as supported by our experimental and theoretical observations. Consistently, the most electron-deficient superoxide adduct shows the strongest driving force for PCET, whereas the most electron-rich system remains unreactive. The pivotal role of these findings in understanding significant heme systems in biology, as well as in alternative energy applications is also discussed.